The Consumer Labeling Initiative - Frederick M. Fishel (EDIS)
This guide explains the objectives, rationale and process of the Environmental Protection Agency's (EPA) Consumer Labeling Initiative. This document is PI-45, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2005.